2020
DOI: 10.3390/cells9061367
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic T-Cell Receptor Replacement—An “Enabler” for TCR-Based Therapies

Abstract: Natural adaptive immunity co-evolved with pathogens over millions of years, and adoptive transfer of non-engineered T cells to fight infections or cancer so far exhibits an exceptionally safe and functional therapeutic profile in clinical trials. However, the personalized nature of therapies using virus-specific T cells, donor lymphocyte infusion, or tumor-infiltrating lymphocytes makes implementation in routine clinical care difficult. In principle, genetic engineering can be used to make T-cell therapies mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 127 publications
0
16
0
Order By: Relevance
“…It could be demonstrated that investigations in the TCR repertoire can help to develop new biomarkers. Furthermore, new therapeutic options were established in cancer therapy using engineered T cell subsets ( 78 , 79 ). Whether these advantages are suitable for clinical application and could be transferred to chronic infections and autoinflammatory diseases is still a topic of research ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could be demonstrated that investigations in the TCR repertoire can help to develop new biomarkers. Furthermore, new therapeutic options were established in cancer therapy using engineered T cell subsets ( 78 , 79 ). Whether these advantages are suitable for clinical application and could be transferred to chronic infections and autoinflammatory diseases is still a topic of research ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“… 99 Especially, T cells with orthotropic T-cell receptor replacement, which preserve near-physiological function, seem like a promising way forward. 100 Worth mentioning, a recent study revealed a dynamic dysfunctional immune macroenvironment, the immune system beyond the tumor microenvironment, due to the cancer burden. 101 Hence, it is possible that even freshly sourced T cells from the blood of some cancer patients may be dysfunctional.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Therefore, measures to prevent TCR mispairing, like murinization of constant TCR chains [ 162 ], codon optimization, cysteineization [ 163 ], or disruption of the endogenous TCR genes is imperative. In the past, the latter has necessitated additional manipulation with e.g., ZFNs, TALENs [ 83 , 84 ], or RNA interference (RNAi) [ 161 , 164 , 165 ], but can now be accomplished concomitantly with the TCR transfer, using newer, TCR locus-specific CRISPR-based gene editing methods [ 79 , 166 , 167 ]. The resulting T cells show physiological regulation and higher expression levels of the introduced TCRs [ 161 , 167 , 168 ], superior antitumor activity in vivo, and reduced GvHD mortality [ 83 , 161 , 164 , 166 ].…”
Section: Critical Tasksmentioning
confidence: 99%